Transport properties of slurries in simulated fracture channels - Junin, Radzuan; Hall, S. T.; Waller, M. D. (1996)
This paper presents the results of a laboratory study of the transport properties of simulated ground drilling waste slurries in vertical channels. The effects of variables such as bulk velocity, solids concentration, particle size, fluid rheological properties and fracture width are presented. The most significant variable are particle size and fluid rheological properties. Bulk velocity and solids concentration were moderately influential and slot width was found to be the less significant.